Thermally Grown MoSe2Thin Film Based MSM Broadband Photodetector - Singh S.; Jit S. (My University, 2025)
An Ag/MoSe2 thin film/Ag structure based metal-semiconductor-metal (MSM) broadband photodetector fabricated on SiO2 coated Si substrate is reported in this letter. The nano-powder synthesized by the hydrothermal route was used for fabricating MoSe2 thin film by thermal evaporation technique. The interdigitated Ag Schottky contacts were fabricated on the MoSe2 film by thermal evaporation method to obtain the desired structure. Photoresponse of the proposed MSM device was measured using monochromatic light of 300 nm-1100 nm. The response showed the maximum responsivity, detectivity and external quantum efficiency (EQE) of ~50 mA/W, sim 4.5times 10^{11} Jones and sim ~16 % respectively at 415 nm (incident power density of sim 70~mu W/cm2) under the applied bias voltage of 1.5 V. The fabricated device also shows fast time response with rise (fall) time as 17.8 ms (18.3 ms). © 1989-2012 IEEE.